Error correction and uncertainty measurement of short-open-load calibration standards on a new concept of software defined instrumentation for microwave network analysis - M. Nazrin (Journal of Measurements in Engineering, 2019)
Software-Defined Radio (SDR) has appeared as a sufficient framework for the development and testing of the measurement systems such as a signal generator, signal analyzer, and network analysis used in the network analyzer. However, most of researchers or scientists still rely on commercial analyzers were larger benchtop instruments, highly cost investment and minimum software intervention. In this paper, a new concepts measurement revolution called as Software Defined Instrumentation (SDI) on network analysis is presented, which is based on reconfigurable SDR, a low-cost implementation, ability to access RF chain and utilizing open source signal processing framework. As a result, a Vector Network Analyzer (VNA) has been successful implemented by deploying an SDR platform, test sets, and data acquisition from the GNU Radio software in host PC. The known calibration process on SHORT-OPEN-LOAD (SOL) technique is validated to ensure measurement data from this SDI free from systematic error. Two types of SOL calibration standards used for a comparison study to validate the SDI measurement system which is capable of generating the response on the differential of standard quality and accuracy of standards kits. Finally, calibration uncertainty analysis is also presented in this work by utilizing RF open source package without any cost addition.